Police innovation contrasting perspectives - Weisburd, David 1954-; Braga, Anthony Allan 1969- (Cambridge University Press, 2019)
Over the last forty years, policing has gone through a period of significant change and innovation. The emergence of new strategies has also raised issues about effectiveness and efficiency in policing, and many of these proactive strategies have become controversial as citizens have asked whether they are also fair and unbiased. Updated and expanded for the second edition, this volume brings together leading police scholars to examine these key innovations in policing. Including advocates and critics of each innovation, this comprehensive book assesses the impacts of police innovation on crime and public safety, the extent of implementation of these new approaches in police agencies, the dilemmas these approaches have created for police management, and their impacts on communities